Broad and Narrow Heritabilities of Quantitative Traits in a Founder Population - Abney, Mark (The American Society of Human Genetics, 2001)
Estimation of the components of variance for a quantitative trait allows one to evaluate both the degree to which genetics influences the trait and the trait’s underlying genetic architecture. For particular traits, the estimates also may have implications for discriminating between potential models of selection and for choosing an appropriate model for linkage analysis. Using a recently developed method, we estimate the additive and dominance components of variance—or, equivalently, the narrow and broad sense heritabilities—of several traits in the Hutterites, a founder population with extensive genealogical records. As a result of inbreeding and because Hutterite individuals are typically related through multiple lines of descent, we expect that power to detect dominance variance will be increased relative to that in outbred studies. Furthermore, the communal lifestyle of the Hutterites allows us to evaluate the genetic influences in a relatively homogeneous environment. Four phenotypes had a significant dominance variance, resulting in a relatively high broad heritability. We estimated the narrow and broad heritabilities as being, respectively, .36 and .96 for LDL, .51 and 1.0 for serotonin levels, and .45 and .76 for fat free mass (FFM). There was no significant additive component for systolic blood pressure (SBP), resulting in a narrow heritability of 0 and a broad heritability of .45. There were several traits for which we found no significant dominance component, resulting in equal broad and narrow heritability estimates. These traits and their heritabilities are as follows: HDL, .63; triglycerides, .37; diastolic blood pressure, .21; immunoglobulin E, .63; lipoprotein(a), .77; and body-mass index, .54. The large difference between broad and narrow heritabilities for LDL, serotonin, FFM, and SBP are indicative of strong dominance effects in these phenotypes. To our knowledge, this is the first study to report an estimate of heritability for serotonin and to detect a dominance variance for LDL, FFM, and SBP.